Penerapan Teknologi Digital untuk Operasional dan Layanan UMKM Florist - Rindiany, Rena (Journal of Informatics Management and Information Technology, 2025)
Florist MSMEs face challenges in managing operations and reaching a broader customer base. This study aims to analyze the use of digital technology to improve operational efficiency and service quality at Rndyaniii Florist, an MSME located in Rantauprapat. The research method used is a case study with a descriptive qualitative approach through observation, interviews, and documentation. Rndyaniii Florist utilizes various digital platforms such as Instagram, Facebook, TikTok, and WhatsApp Business for promotion, communication, and product ordering. In addition, the store also uses a website based on Google Sites as a digital catalog to facilitate customer access to product information. This study is important to examine how digital technologies such as social media, communication applications, and simple websites can be effectively implemented in the context of florist MSMEs. Preliminary findings indicate that consistent use of digital platforms can accelerate the ordering process, enhance customer interaction, and expand market reach. Digitalization also supports daily operational efficiency and builds a more professional business image. This research provides a concrete overview of digitalization strategies that can be applied by other florist MSME owners, especially in facing increasingly technology-based market competition.